2021
DOI: 10.2147/ott.s298655
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Osimertinib and Anlotinib May Overcome the Resistance Mediated by in cis EGFR T790M-C797S in NSCLC: A Case Report

Abstract: The emergence of epidermal growth factor receptor ( EGFR ) exon 20 p.C797S is one of the major resistance mechanisms for osimertinib. However, there are no standard of care for non-small cell lung cancer (NSCLC) patients after acquiring EGFR C797S currently, which brings significant challenges to post-osimertinib clinical management. In the present study, we described a 52-year-old female patient with EGFR -mutated stage IV lung adenocarcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The conclusion indicated that apatinib plus osimertinib might play a synergistic action and improved the clinical outcomes for patients with osimertinib refractory EGFR‐positive NSCLC. Besides, a recent study initiated by Zhou and colleagues reported one patient with cis EGFR T790M‐C797S NSCLC 26 . After the failure of osimertinib therapy, this patient was treated with the combination of anlotinib plus osimertinib as maintenance therapy and achieved PR response of 9 months, which suggested that anlotinib plus osimertinib administration might overcome osimertinib resistance and improve PFS for the patients.…”
Section: Discussionmentioning
confidence: 92%
“…The conclusion indicated that apatinib plus osimertinib might play a synergistic action and improved the clinical outcomes for patients with osimertinib refractory EGFR‐positive NSCLC. Besides, a recent study initiated by Zhou and colleagues reported one patient with cis EGFR T790M‐C797S NSCLC 26 . After the failure of osimertinib therapy, this patient was treated with the combination of anlotinib plus osimertinib as maintenance therapy and achieved PR response of 9 months, which suggested that anlotinib plus osimertinib administration might overcome osimertinib resistance and improve PFS for the patients.…”
Section: Discussionmentioning
confidence: 92%
“…2). Infrequent cases showed triple mutation with C797S in cis may benefit from the combination of osimertinib and anlotinib, the combination of afatinib and apatinib [79,80].…”
Section: Mapk Pathway > Braf V600ementioning
confidence: 99%
“…Osimertinib plus anlotinib or afatinib plus apatinib achieved a partial response of 9 months and a PFS of more than 10 months in two case reports, respectively. These suggest that combination of EGFR inhibitors and VEGFR inhibitors is a promising therapy for EGFRmutated NSCLC patients with T790M in cis with C797S [116,117]. Recently, an immune checkpoint inhibitor (ICI) combined with platinum-based doublet chemotherapy also exhibited efficacy against T790M-cis-C797S, with a PFS of 8 months, which should be further evaluated in clinical trials [118].…”
Section: Combination Of First-and Third-generation Egfr-tkis Inmentioning
confidence: 99%